2006
DOI: 10.1111/j.1742-7843.2006.pto_339.x
|View full text |Cite
|
Sign up to set email alerts
|

Veratridine‐Induced Wet Dog Shake Behaviour and Apoptosis in Rat Hippocampus

Abstract: Abstract:We have previously evaluated veratridine as an in vitro model of seizure using conventional electrophysiological recordings in rat hippocampal CA1 pyramidal neurones. The aim of this investigation is to further characterize this convulsant as an in vivo model of seizure. Veratridine was administered intraperitoneally to male Fisher rats in a dose range of 100-400 mg/kg. Within 5 min. after the injections, the animals entered a quiescent period which was followed 10-15 min. later by facial automatism (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Veratridine‐induced neuronal death, like that of KA, is also associated with induction of p53 and apoptosis‐related signalling (Jordan et al. 2003; Otoom et al. 2006).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Veratridine‐induced neuronal death, like that of KA, is also associated with induction of p53 and apoptosis‐related signalling (Jordan et al. 2003; Otoom et al. 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, we examined ER stress and injury responses using an alternative seizure‐like injury. Veratridine, a sodium channel activator, induces hippocampal pyramidal neuron burst‐firing, seizures and neuronal death (Alkadhi and Tian 1996; Otoom et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 -40 WDS has also been considered to indicate stress [41][42][43] and pain 44,45 and is regulated by 5-Ht-activation. [46][47][48] An increase in grooming and WDS may thus indicate that the rats experience some form of discomfort. If this is in anyway related to low back pain is not possible to understand from the present investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of wet dog shakes (WDS) has been widely used in psychopharmacological studies and is a typical sign of withdrawal from opiates, benzodiazepines and barbiturates [10-14]. WDS has also been considered to indicate stress [15-17] and pain [18, 19] and is regulated by 5-Ht-activation [20-22]. Although it was not possible to draw any conclusions if grooming and WDS could correspond to disc induced low back pain, it was concluded that the findings seemed to indirectly support such hypothesis [1].…”
Section: Discussionmentioning
confidence: 99%